2017
DOI: 10.1504/eg.2017.10004264
|View full text |Cite
|
Sign up to set email alerts
|

How perceived effort expectancy and social influence affects continuance of intention to use e-government. A study of a Malaysian government service

Abstract: This study examines the role of effort expectancy and social influence in explaining Malaysian government service acceptance of e-government services from the perspective of Malaysian government servants. The paper is based on survey data (n = 543) collected in Pahang, Malaysia between April 2014 to July 2014 and was analysed by using SPSS 20 (Statistical Package for the Social Sciences). The analysis of data was performed by a combination of exploratory factor analysis (EFA) and multiple linear regressions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…User habits had a significant effect on behavioral intention. The results of the analysis for construct facilitating conditions were in line with the results of previous studies on online learning, which state that there is a significant relationship between facilitating conditions and behavioral intention (Razak et al, 2017;Masadeh et al, 2016;Raman & Don, 2013). Factors such as lack of assistance and timely support, incomplete information, and limited resources can prevent individuals from accepting web-based technology (Masadeh et al, 2016).…”
Section: Resultssupporting
confidence: 85%
“…User habits had a significant effect on behavioral intention. The results of the analysis for construct facilitating conditions were in line with the results of previous studies on online learning, which state that there is a significant relationship between facilitating conditions and behavioral intention (Razak et al, 2017;Masadeh et al, 2016;Raman & Don, 2013). Factors such as lack of assistance and timely support, incomplete information, and limited resources can prevent individuals from accepting web-based technology (Masadeh et al, 2016).…”
Section: Resultssupporting
confidence: 85%
“…The effect of social influence on the behavioral intention to use a new or adapted technology is well known. For example, previous studies have already shown that social influence has an impact on the behavioral intention to use mobile-based assessments [ 37 ], Instagram messaging [ 38 ], web-based banking [ 39 ], eHealth services [ 40 ], social media [ 41 ], e-government [ 42 ], e-learning [ 43 ], and accounting platforms [ 44 ]. Although this review is not exhaustive and includes only a fraction of the studies that have investigated the relationship between social influence and the behavioral use intention, to the best of our knowledge, the relationship between social influence and behavioral intention to use PRWs has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%